Effect of Various Rates of Manure on Growth and Yield of Sesame (Sesamum indicum L.) in Sandy Land Area - Marwansyah Barus, Rohlan Rogomulyo, dan Sri Trisnowati (Universitas Gadjah Mada, 2013)
ABSTRACTThis research was conducted to determine the rate of manure most appropriate for growth and yield of sesame (Sesamum indicum L.) in sandy land area. The experiment was located at the sandy land area of Keburuhan, Purworejo. The design used was a complete randomized block design (RAKL) with three blocks as replication. The treatments applied were various rates of cattle manure consisted of 5 levels, namely: 20 ton/ha, 40 ton/ha, 60 ton/ha, 80 ton/ha, and 100 ton/ha .The results showed that the application of 20 ton/ha to 100 ton/ha manure did not increase plant height, number of pods, number of flowers, and net assimilation rate of sesame. Fertilizer application at the rate of 60 ton/ha produced the highest number of leaves, while the highest plant fresh weight obtained at 80 tons/ha. 40 ton/ha and 80 ton/ha of manure produced the highest crop growth rate (CGR), which resulted in higher plant dry weight. Increasing manure rate did not significantly increase the yield of sesame seeds.Keywords: sesame, sandy land, manure